Implementing NAP and NAC security technologies : the complete guide to network access control - Hoffman, Daniel (Daniel V.), 1972- (Wiley Pub., 2008)
"You're ready to see through the misconceptions and misinformation about NAP/NAC that might come your way. Here is an excellent resource for uncovering the actual vulnerabilities and exploits that the various NAP/NAC types can address. You'll find real-world hacking scenarios, along with complete implementation guidance for the right NAP/NAC solution. This guide will help you determine what type of solution makes the most sense, based upon the most prevalent risks in your environment."--Jacket